THE INFLUENCE OF PROMOTIONS ON DECISIONS SITINJAK VILLAGE COMMUNITY USING SAVING PRODUCTS HAJJ IN SHARIA BANK - annisa yuliana; fatahuddin siregar; adanan murrah; veri pramudia (Journal Of Sharia Banking, 2020)
Without promotion, it is not expected that customers can get to know the bank, therefore, promotion is the most effective means of attracting and retaining customers. One of the objectives of bank promotion is to inform all types of products offered and try to attract new prospective customers. Promotion is not only a communication tool between companies and customers, but also as a tool to influence customers. Customer decisions are alternative choices of decisions made by customers to use the products offered by the company. This research is a quantitative study using simple regression analysis. The collection technique used by researchers in this study is to use a questionnaire and through observation of individuals whose information is needed in this study. Questionnaire is a data collection technique that is done by giving a set of statements or written questions to respondents to be answered. The sample used in this study were 34 respondents. Data processing is done with SPSS version 22. The results of the coefficient of determination (R2) can be seen that the R Square value of 0.443 means that the promotion variable is able to explain the decision variable to be a customer by 44.3 percent while the remaining 55.7 percent is explained by other variables not included in this model. In another sense that there are still variables that influence the decision to become a customer in addition to promotion. Based on the results of this study indicate a significant influence that is the promotion of decisions with a ttable tcount (2.036 5.041).